Immune Thrombocytopenic Purpura as an Extraintestinal Manifestation in a Patient with Ulcerative Colitis - De Medeiros Dutra, Renata [UNESP]; Almeida, Luciana Rocha [UNESP]; Sinkos, Camila [UNESP]; Muraro Bonini, Ana Clara [UNESP]; Saad-Hossne, Rogerio [UNESP]; Baima, Julio Pinheiro [UNESP]; Sassaki, Ligia Yukie [UNESP] (Karger Publishers, 2022)
Immune thrombocytopenic purpura (ITP) is characterized by the presence of autoantibodies against platelet membrane antigens, leading to immune-mediated platelet destruction. ITP is considered as a rare extraintestinal manifestation (EIM) of ulcerative colitis (UC). This report aimed to describe a rare case of UC associated with ITP and a review of the literature. A 49-year-old man was admitted to our hospital with severe acute colitis which was responsive to treatment (hydrocortisone 300 mg/day). The patient was discharged from the hospital with prednisone 60 mg/day and azathioprine 50 mg/day. During the follow-up, the dose of azathioprine was increased to 100 mg/day (1.3 mg/kg), while prednisone tapering was started. After 3 months, the patient presented with thrombocytopenia (30,000 platelets/μL) without improvement despite receiving the suspension of azathioprine; thus, a bone marrow aspirate was performed. The bone marrow analysis showed hyperplasia of the erythroid series, megaloblastosis, hyperplasia of megakaryocytes with mild dyspoiesis, and absence of cytotoxicity, a morphological finding consistent with ITP. The patient was treated with prednisone 1 mg/kg/day which resulted in partial improvement of the condition and his still being followed up as outpatient using mesalazine 3.2 g for UC and a platelet count of approximately 50,000/μL using eltrombopag. As reported, ITP is a rare EIM in patients with UC. Due to the risk of complications, such as bleeding, hematological changes in these patients should be considered. The disease should be suspected in the presence of thrombocytopenia, always excluding the side effects of medications in advance, especially immunosuppressants. The correct diagnosis of this rare manifestation and proper treatment are essential to control the condition, prevent complications, and improve the patient's prognosis.
Keywords: Immune thrombocytopenic purpura; Inflammatory bowel disease; Ulcerative colitis